2006
DOI: 10.1139/g06-125
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of Coffea arabica L. leaves and roots to chemically induced systemic acquired resistance

Abstract: Coffea arabica is susceptible to several pests and diseases, some of which affect the leaves and roots. Systemic acquired resistance (SAR) is the main defence mechanism activated in plants in response to pathogen attack. Here, we report the effects of benzo(1,2,3)thiadiazole-7-carbothioic acid-S-methyl ester (BTH), a SAR chemical inducer, on the expression profile of C. arabica. Two cDNA libraries were constructed from the mRNA isolated from leaves and embryonic roots to create 1587 nonredundant expressed sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 77 publications
5
24
0
Order By: Relevance
“…Also, there were metallothioneins, cysteine-rich proteins that bind to heavy metals. The metallothioneins are upregulated during the development of fruits and they are a systemic response for abiotic stress (Moyle et al 2005;De Nardi et al 2006). Also, an embryo-specific protein 3 that participates in seed development (Girke et al 2000), an auxin receptor F box protein that regulates auxin response, implicated in every aspect of plant growth and development (Dharmasiri et al 2005), and a cupin family protein, which includes many of the storage proteins from higher plants and nutrient reservoir activity (Dunwell et al 2000), were found.…”
Section: Number Of Sequencesmentioning
confidence: 99%
“…Also, there were metallothioneins, cysteine-rich proteins that bind to heavy metals. The metallothioneins are upregulated during the development of fruits and they are a systemic response for abiotic stress (Moyle et al 2005;De Nardi et al 2006). Also, an embryo-specific protein 3 that participates in seed development (Girke et al 2000), an auxin receptor F box protein that regulates auxin response, implicated in every aspect of plant growth and development (Dharmasiri et al 2005), and a cupin family protein, which includes many of the storage proteins from higher plants and nutrient reservoir activity (Dunwell et al 2000), were found.…”
Section: Number Of Sequencesmentioning
confidence: 99%
“…The mechanism of BTH induced resistance is activation of the plant defense genes and expression resistance-related proteins or enzymes [10]. The defense-related genes of BTH induced diseases resistance to rice, wheat [11], cucumber [12], papaya [13], coffee [14], cocoa [15] and so on were identified and analysed. In rubber tree susceptible clone against the diseases, the peroxidase, phenylalanine aminolyase and β-1,3 glucanase are increasing significantly in leaves after BTH treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…All together, a significant set of 55,692 ESTs, mainly from fruits, is already publicly available for C. canephora (Table 9.1). Regarding C. arabica, public accessibility to EST collections is limited to 1,226 ESTs, comprising a suppression subtractive hybridization library of 618 EST sequences selected upon infection by H. vastatrix , 139 EST sequences identified as a differential response of C. arabica leaves and roots to chemically induced systemic acquired resistance (De Nardi et al 2006), and 469 other ESTs from leaves (Cristancho et al 2006;Joet et al 2006). In total, there are fewer than 60 thousand entries of coffee ESTs, publicly available, deposited at the dbEST database.…”
Section: Coffee Est Resourcesmentioning
confidence: 99%
“…Aiming at the development of EST-SSR markers for coffee, an Indian research group reported an interim set of 2,092 ESTs of coffee generated at CCMB (Center for Cellular & Molecular Biology), Hyderabad, India (Aggarwal et al 2007). EST sequences of two cDNA libraries from leaves and embryonic roots of C. arabica were also produced by an Italian group to develop a cDNA microarray based on 1,587 non-redundant sequences (De Nardi et al 2006).…”
Section: Coffee Est Resourcesmentioning
confidence: 99%